Moringa oleifera Seed Oil (MOSEIL) Reduce CTGF (Connective Tissue Growth Factor) Gene Expression in Mice (Mus musculus) Liver Fibrosis Models - Susanto Hendra; Melani Inriana Candra; Negara Diajeng Ravika Adil Bangun; Nurfadila Wafiq Azizah; Azizah Khulud Rizqi; Zahira Hasnawati; Malek Nik Ahmad Nizam Nik (BIO Web of Conferences)
Liver fibrosis is a chronic liver disease that accounts for 45% of all causes of death in the world. Treatment for liver fibrosis until this day only uses synthetic drugs based on the cause. There are many side effects from synthetic drugs, so it is necessary to look for natural traditional medicines to treat liver fibrosis. One plant that has potential as an antifibrotic agent is Moringa oleifera seeds. This research aims to determine the effect of Moringa oleifera seed oil (MOSEIL) on mice (Mus musculus) with liver fibrosis models to develop drugs and prevent liver fibrosis. This study used 30 Balb/C mice that injected intraperitoneally with CCl4 and MOSEIL for 8 weeks. Body weight was measured once a week during treatment. The liver is weighed after dissection. Mice livers were taken to see the level of liver inflammation through histology and RT-qPCR tests to see CTGF gene expression. Data were analyzed using ANOVA with Duncan's post hoc test. Histological test results showed that MOSEIL could reduce necrosis and inflammation in the group given MOSEIL. CCl4 caused a significant reduction in the body weight of mice, while the results of the ANOVA on mice liver weight were not significant. Mice treated with MOSEIL had decreased CTGF gene expression compared to mice not treated with MOSEIL. This research requires further exploration and formulation of the active ingredients of Moringa oleifera seeds to prove further that MOSEIL has potential as an anti-liver fibrosis drugs.